Если \(x = 5 - 5 ^ ( 2/3) - 5 ^ (1/3)\), докажи это \( x ^3 - 15x^2 + 60 x - 20 = 0\)?

0
0

Если \(x = 5 — 5 ^ ( 2/3) — 5 ^ (1/3)\), докажи это \( x ^3 — 15x^2 + 60 x — 20 = 0\)?

0
0

Пожалуйста, смотрите доказательство в объяснении.

Объяснение: \[x=5-5^(2/3)-5^(1/3)\] , \[:. 5-x=(5^(2/3)+5^(1/3))…………(ast)\] , \[:. (5-x)^3=(5^(2/3)+5^(1/3))^3\] , \[:. 5^3-x^3-3(5)(x)(5-x)=(5^(2/3))^3+(5^(1/3))^3\] \[+3xx5^(2/3)xx5^(1/3)(5^(2/3)+5^(1/3)), i.e., \] \[125-x^3-75x+15x^2=5^2+5^1+3xx5xx(5-x)…[because, (ast)]\] \[:. 125-75x+15x^2-x^3=30+75-15x\] , \[:. 20-60x+15x^2-x^3=0,\] по желанию!

Показан 1 результат